Efficacy, Tolerability and Adverse Effects of Triple Fixed Dose Combination Brimonidine–Brinzolamide–Timolol Ophthalmic Suspension in Primary Open Angle Glaucoma: A Retrospective Study - Hina Kounsar; Swati Singh; Harsh Kumar (Delhi Journal of Ophthalmology)
Purpose: To evaluate the efficacy and tolerability of recently introduced triple fixed dose combination (TFC) of brimonidine–brinzolamide–timolol (BBTFC) in patients with primary open angle glaucoma (POAG). Materials and Methods: A retrospective review was done in POAG patients who were shifted to triple fixed dose combination of BBTFC. Patients were divided into two groups: Group A had 30 eyes with all three components as dual fixed + single (2 + 1) or 3 unfixed (1 + 1 + 1) component drugs and Group B had eight eyes with only two-component drugs of TFC in previous regimens. Intraocular pressure (IOP) was measured at baseline before change and at 1 week and 4 weeks after change. Any new ocular and systemic side effects experienced by the patients were noted. Results: We found 38 eyes of 22 patients (16 males and 8 females) where BBTFC was started. The mean IOP was 20.42 ± 3.26 mmHg at baseline, 18.37 ± 2.68 mmHg with a 10% reduction at 1 week, and 16.47 ± 2.00 mmHg with a 19.34% reduction at 4 weeks. In Group A, the mean IOP was 16.46 mmHg with 11% reduction at 4 weeks. The mean baseline IOP in Group B (22.87 mmHg) was significantly higher than in Group A (19.77 mmHg) (P = 0.01). By shifting to BBTFC and addition of one more drug to the treatment, the IOP reduction was 6.37 mmHg (27.8%) in this group. The common side effects were hyperemia and itching which were not severe except in two patients where drug was withdrawn at 1 week because of severe intolerance. Conclusion: Addition of BBTFC resulted in significant IOP reduction and fair tolerability profile in short-term follow-up. It can be considered for a better IOP control in POAG patients.